Identifying potential for rice expansion in Burkina Faso: integrating EO and climate data for suitability mapping - Meier, Jonas; Hirner, Andreas; Akpoti, Komlavi; Hackman, Kwame; Gessner, Ursula (Frontiers in Climate, 2025)
Over the last years, food security in West Africa has been strongly influenced by increasing weather variability, including rising temperatures, irregular precipitation patterns, and more frequent extreme events. These factors threaten traditional rain-fed agriculture, while population growth and urbanization are driving greater demand for rice—a crop increasingly replacing traditional staples. To reduce dependency on imports, West African countries are seeking to expand domestic rice production. Inland valleys and floodplains, due to their high water retention and fertile soils, offer significant but underutilized potential for rice cultivation. To assess the suitability and current extent of rice cropping, we selected Burkina Faso as a representative country in West Africa that exemplifies the challenges outlined above. Inland valleys were delineated using a digital elevation model (SRTM), and rice cropping areas in 2020 were mapped using a random forest classifier applied on Sentinel-1 and Sentinel-2 satellite time series. The classification was based on temporal-spectral metrics, including vegetation indices such as NDVI and backscatter statistics, and validated against reference samples to assess accuracy. Climatic suitability from 1999 to 2021 was evaluated using ERA5-Land reanalysis data, based on crop growth requirements of rice across different growth stages. Only 0.71% of Burkina Faso’s land is currently used for rice cropping, closely matching national FAO statistics (0.74%) and independent mapping efforts. However, approximately 10% of the national territory consists of inland valleys, which are biophysically suitable for rice cultivation. While the southwestern regions show relatively stable climatic suitability, the central and northern areas are more variable and vulnerable to drought, limiting their long-term potential without irrigation. The integration of climatic suitability and landform-based potential highlights considerable opportunities for expanding rice cultivation in Burkina Faso. This study provides a spatial decision-support framework for policymakers to guide sustainable intensification, reduce import dependency, and adapt agricultural systems to climate change.